Interface manipulation towards wrinkle-free forming of stacked UD prepreg layers. (November 2016) - Hallander, P.; Sjölander, J.; Petersson, M.; Åkermo, M.
Abstract: The aim of this paper is to experimentally study how forming behaviour can be changed by local manipulation of prepreg interfacial characteristics. Different methods for surface modification are examined, however all were aimed at enabling significantly increased interply friction. The paper shows that by using increased friction in between layers, these neighbouring pairs will act together during forming, thereby either improving or exacerbating the forming outcome. For the geometry utilized, wrinkle free forming was obtained when the cross-plied layers were paired to deform mainly through intraply shear during forming. The method is supported by the appended numerical analysis and interaction between forming mechanisms and radius thinning is instigated as part of the experimental outcome.